Transnational Networks of Pork Production: Fragile Linkages between Germany and CEE Countries - Klein, Oliver (European Spatial Research and Policy, 2018)
The intention of this paper is to explore the internationalization efforts of German pork producers towards Central and Eastern Europe (CEE) with a special focus on recent dynamics, market development strategies and policy conditions. The added-value potentials offered by CEE countries have become increasingly lucrative for the German pork industry, particularly as the domestic market currently shows a certain degree of saturation in terms of consumption. The results of this study which is mainly based on qualitative interviews with selected pork producers from North-West Germany reveal that transnational pork production networks between Germany and CEE are shaped by a high degree of fragility and discontinuity. This is reflected not only by the fluctuating development of foreign trade in piglets, live hogs and pork products, but also by the uncertainty and hesitancy of the interviewed pork producers with regard to business operations in CEE markets. It will be shown that the policy conditions on the national level still have a clear impact on internationalization processes in the pork industry. The paper further illustrates that the configuration of transnational pork production networks can be explained, in part, by insights from the global production networks (GPN) and the agri-food geographies literature.